The Impact of Proactive Personality on Career Decision-Making Self-Efficacy: The Role of AI Acceptance and Innovation Skills - Kunji Li; Jeffery D. Houghton; Siyu Chen; Xuan Li; Danyang Li; Wenchi Zou (Behavioral Sciences)
This study aimed to investigate the relationship between proactive personality and career-related decision-making self-efficacy, with generative artificial intelligence acceptance serving as a mediating factor. Additionally, the study examined the moderating effect of innovation competencies on this mediation pathway, utilizing a moderated mediation framework. The study included 501 university students from Guangdong Province, China, who completed validated measures of proactive personality, career-related decision-making self-efficacy, generative artificial intelligence acceptance, and innovation competencies. Data analysis was conducted using SPSS (Version 26) and the PROCESS macro to evaluate mediation, moderation, and moderated mediation effects. Moreover, confirmatory factor analysis was performed using Amos (Version 28.0) to assess the validity of the measurement models. The results indicate that proactive personality exerts an indirect effect on career-related decision-making self-efficacy via generative artificial intelligence acceptance. The strength of this indirect effect was moderated by innovation competencies, indicating that the relationship is stronger at higher levels of innovation competencies. These findings contribute to a more nuanced understanding of the relationship between proactive personality and career-related decision-making self-efficacy, particularly within the context of technological adaptability.